Capturing 3D Water Flow in Rooted Soil by Ultra-fast Neutron Tomography - Christian Tötzke (Nature Portfolio, 2017)
Abstract Water infiltration in soil is not only affected by the inherent heterogeneities of soil, but even more by the interaction with plant roots and their water uptake. Neutron tomography is a unique non-invasive 3D tool to visualize plant root systems together with the soil water distribution in situ. So far, acquisition times in the range of hours have been the major limitation for imaging 3D water dynamics. Implementing an alternative acquisition procedure we boosted the speed of acquisition capturing an entire tomogram within 10 s. This allows, for the first time, tracking of a water front ascending in a rooted soil column upon infiltration of deuterated water time-resolved in 3D. Image quality and resolution could be sustained to a level allowing for capturing the root system in high detail. Good signal-to-noise ratio and contrast were the key to visualize dynamic changes in water content and to localize the root uptake. We demonstrated the ability of ultra-fast tomography to quantitatively image quick changes of water content in the rhizosphere and outlined the value of such imaging data for 3D water uptake modelling. The presented method paves the way for time-resolved studies of various 3D flow and transport phenomena in porous systems.